Early long-term low-dosage colchicine and major adverse cardiovascular events in patients with acute myocardial infarction: a systematic review and meta-analysis - Zhou, Yifang; Liu, Yidan; Zeng, Ruixiang; Qiu, Wenjie; Zhao, Yunhong; Zhou, Yuanshen (Frontiers in Cardiovascular Medicine, 2023)
Background Current evidence on the efficacy and safety of colchicine after acute myocardial infarction (AMI) remains controversial. This study aims to clarify early low-dose long-term colchicine's exact efficacy and safety in AMI patients via more studies. Methods We searched PubMed, Web of Science, Embase, and Cochrane Library databases for randomized controlled trials assessing the efficacy of colchicine on major adverse cardiovascular events (MACE) in recent AMI patients from inception to January 29, 2023, without any restriction. Additionally, we conducted subgroup analyses to assess the impact of early (≤3 days) long-term (≥1 year) low-dosage (0.5 mg/d) colchicine. Summary estimates were computed using Mantel-Haenszel and reported as risk ratios (RRs) or standard mean differences (SMDs), mean differences (MDs) with 95% confidence intervals (CIs). Sensitivity analyses were performed to explore the potential sources of heterogeneity. Review Manager software was used for the meta-analysis. Results Eight studies identified from 564 screened records were analyzed, with 5,872 patients after AMI. The length of follow-up varied from five days to 22.7 months, and 0.5–1.0 mg colchicine was administered daily. In summary, compared to the control group, colchicine reduced the occurrence of MACE (RR, 0.56; 95% CI, 0.48–0.67) with 2.99-fold gastrointestinal adverse events in patients with recent AMI. Moreover, the relation referred to a gradual decrease in the occurrence of MACE with a longer follow-up duration (≥1 year) and lower dosage (0.5 mg/d) without leading more gastrointestinal adverse events. Colchicine decreased the follow-up levels of C-reactive protein (CRP) (MD −0.66, 95% CI, −0.98– −0.35) and neutrophils (SMD −0.22, 95% CI, −0.39– −0.55) when the follow-up period was 30 days. Conclusion Early long-term low-dose colchicine decreases the risk of MACE via anti-inflammation without leading more gastrointestinal adverse events in patients with AMI.